2011
DOI: 10.2478/v10026-011-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenol oxidation with hydrogen peroxide using Cu/ZSM5 and Cu/Y5 catalysts

Abstract: In this work, catalytic activity and stability of Cu/Y5 and Cu/ZSM5 zeolites in phenol oxidation with hydrogen peroxide were examined. The catalyst samples were prepared by the ion exchange method of the protonic form of commercial zeolites. The catalysts were characterized by the powder X-ray diffraction (XRD), AAS, while the adsorption techniques were used to measure the specific surface area. The thermal programmed desorption of NH3 (NH3-TPD) was used for measuring the total number of acid sites formed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Increasing pH value from 2-3 favoured the decolorization of RB4 while the higher pH value (pH >3) decreased the catalytic activity. The maximum decolorization efficiency of RB4 was achieved at pH 2.5 with 98% decolorization efficiency due to enhance formation of highly reactive OH • radical at an acidic condition due to the presence of photons [27]. Similar results were also reported by other researchers in heterogeneous Fenton-like reaction [12], [13].…”
supporting
confidence: 86%
“…Increasing pH value from 2-3 favoured the decolorization of RB4 while the higher pH value (pH >3) decreased the catalytic activity. The maximum decolorization efficiency of RB4 was achieved at pH 2.5 with 98% decolorization efficiency due to enhance formation of highly reactive OH • radical at an acidic condition due to the presence of photons [27]. Similar results were also reported by other researchers in heterogeneous Fenton-like reaction [12], [13].…”
supporting
confidence: 86%
“…The earlier analysis of the effect of surface acidity on the radical mechanism indicated that the lower total acidity and L/B on the surface might be the main factors affecting the reaction rate. The adsorption–desorption mechanism is an important step in heterogeneous catalysis and is influenced by the intrinsic acidity of the solid catalyst [25–28] . In contrast, 20Zr has a higher total acidity, and L/B has a lower reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…Rubalcaba et al (2007) reported that, adding H 2 O 2 to the CWAO process not only increases pollutant removal but also leads to higher mineralisation of the remaining oxidation products. This is because hydrogen peroxide acts as a free radical initiator, providing hydroxyl radicals that increase pollutant removal (Valkaj, 2011). was studied at 0.01 mol/L of maleic acid, 50°C and 0.5 g/l of activated carbons.…”
Section: Conversion (%)mentioning
confidence: 99%